Silica Nanoparticle Enhancement in the Efficiency of Surfactant Flooding of Heavy Oil in a Glass Micromodel - Shirin Alexander (Industrial & Engineering Chemistry Research, 2017)
The synergic effects of fumed-Si nanoparticles (Si-NPs) in combination with sodium dodecyl sulfate (SDS) surfactant as suitable agents for oil displacing in enhanced oil recovery (EOR) are evaluated using a 5-spot glass micromodel. Optimum oil recovery (45%) is obtained for SDS near the critical micelle concentration; however, the addition of fumed silica nanoparticles (Si-NPs) enables a further 13% enhancement in oil recovery for the maximum concentration of the SDS/Si-NPs (2.2 wt.%), as well as delaying the breakthrough point. The optimum mass ratio of SDS:Si-NP (1:11) suggests that the Si-NPs are aggregated by the SDS micelles; consistent with increased viscosity upon addition of Si-NPs. The presence of the Si-NPs also greatly increases the wettability on the glass surface, with a decrease in the contact angle from 73° for SDS (1800 ppm) to 11° for SDS/Si-NPs (1800 ppm/2.0 wt.%). The effective changes in the oil sweeping mechanism are directly observed in glass micromodel and correlate to these physical measurements. The results demonstrated the addition of Si-NPs to SDS solutions made a significant improvement to oil recovery values and potentially beneficial in EOR applications.